Robots, AI, and immigration: A race for talent or of displaced workers - Yvonne Giesing; Britta Rude (EconPol Forum, 2022)
Adoption of new technologies can affect different skill groups differently, potentially increasing inequality between migrant and native populations. New technologies often create skill shortages. Industrial robots and artificial intelligence have important beneficial labor market effects on natives, but not migrants. We observe an increase in the immigrant inflow as a response to AI adoption. Policymakers should pay special attention to the migrant population when designing mitigation policies in response to automation.
Keywords: 330